2018
DOI: 10.1016/j.matchemphys.2017.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Chemically uracil–functionalized carbon and silicon carbide nanotubes: Computational studies

Abstract: h i g h l i g h t s Single standing hybrid nanotube structures have been constructed. Polarizablity of nanotubes has been increased in the hybrid structures. HOMO-LOMO gaps of nanotubes are almost the same in the gas-phase and water-solvated systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Binding energy, total energy, and chemical potential.-The total energy and the binding energy calculations are used to determine the stability of the structures. The binding energy or the cohesive energy can be calculated as, 21…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Binding energy, total energy, and chemical potential.-The total energy and the binding energy calculations are used to determine the stability of the structures. The binding energy or the cohesive energy can be calculated as, 21…”
Section: Resultsmentioning
confidence: 99%
“…For nanotube-assisted drug delivery in pharmaceutical applications, the addition of biological structures to nanotubes is essential. DFT studies carried out by Kun Harismah et al, 21 on uracil functionalized SiCNT hybrids, have identified that in comparison to C-C bonds of CNTs, the Si-C bonds of silicon carbide nanotubes (SiCNTs), were stable and ionic. SiCNTs are not better soluble in water.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To this aim, molecular properties have been evaluated for the original furanone and two of 5H derivatives to explore the effects of structural modifications in addition to molecular orbital properties of new structures (Table 1). Knowledge about subatomic unites properties for chemical structures could help to provide new structures based on desired proposes, which are very much important to introduce new compounds especially for treatments of living systems [13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%